2021
DOI: 10.3390/ijerph18020536
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress in Relation to Quality of Life and Resilience in Patients with Advanced Chronic Kidney Disease Undergoing Hemodialysis

Abstract: Background: Patients with chronic kidney disease undergo various stages of therapeutic adaptation which involve lifestyle modifications, physical changes, and adjustment to renal replacement therapy. This process produces adaptive stress. Objective: To identify how resilience, health- related quality of life, and sociodemographic, clinical, and hemodialysis routine-related variables are related to perceived stress in patients with chronic kidney disease receiving hemodialysis for more than six months. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
0
13
1
11
Order By: Relevance
“…In this study, perceived stress had a significant negative correlation with positive coping styles of patients on MHD, which is consistent with previous research results [ 28 , 29 ]. Our results showed that the score of the Perceived Stress Scale was higher than that reported in a previous study [ 17 ], indicating that patients on MHD perceived higher stress during the COVID-19 pandemic lockdown period. This may have been related to the following.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In this study, perceived stress had a significant negative correlation with positive coping styles of patients on MHD, which is consistent with previous research results [ 28 , 29 ]. Our results showed that the score of the Perceived Stress Scale was higher than that reported in a previous study [ 17 ], indicating that patients on MHD perceived higher stress during the COVID-19 pandemic lockdown period. This may have been related to the following.…”
Section: Discussioncontrasting
confidence: 82%
“…Some patients experience fear and excessive tension, or even mild insomnia and lack of appetite, which makes them unable to respond with a positive attitude. Therefore, perceived stress is an external risk factor for patients with MHD, and the continuous accumulation of perceived stress will damage the patient’s physical and mental health [ 17 ]. Thus, early warning and making interventions are important to prevent the effects of an accumulation of negative life event by relaxing the psychological pressure of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological resilience, defined as an individual's ability to actively mobilize all favorable factors to maintain or restore relatively stable mental and physical functions in the face of stressful life events and adversity ( 11 ), is widely recognized as an individual's competency and strength to successfully cope with stress ( 12 ). Higher psychological resilience is associated with greater acceptance of the disease, higher compliance with therapeutic regimens, and more favorable outcomes in patients with chronic renal diseases ( 13 , 14 ). Lower psychological resilience is associated with emotional dysregulation ( 15 ) and variations in sensory processing ( 16 , 17 ), which can increase the risk of suicidality in some patient populations ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…La PAE hace referencia a las representaciones mentales que tiene la persona de su enfermedad, en relación a la identidad (nombre y síntomas), causas, consecuencias, curso y control de la misma (Lau, Bernard, & Hartman, 1989;Petrie & Weinman, 2012). En este sentido, parece que quienes perciben como más amenazante su enfermedad, presentan más ansiedad, depresión y peor calidad de vida (Broadbent et al, 2015;Chew et al, 2017;García-Martínez et al, 2021;Nowicka-Sauer et al, 2016;Valero-Moreno et al, 2020).…”
Section: Introductionunclassified